Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1300/j064v29n04_06
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nitrogen Fertilization on Intercropped Strawberry and Broad Bean

Abstract: significant differences in fruit weight per plant and total fruit weight of strawberry. Intercropping caused some phenotypic alteration such as increasing height and growth habits of broad bean. However, there were no significant reductions in pod numbers, pod weight per plants and total yield of intercropped broad bean at 80 kg/ha nitrogen application as compared with sole cropping. Strawberry intercropped with broad bean at 80 kg/ha nitrogen gave the best LER values, indicating that intercropping might be mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…2006 and 2007, steadily increasing over time and reaching maximum temperatures above 90°F after Apr. 2006 and2007. Cucurbit planting dates did not affect strawberry aboveground biomass volume as revealed by canopy diameters, which did not change significantly across planting dates, with average diameters of 15.2 and 15.3 inches during 2006 and 2007, respectively (Table 2). This finding indicated that there was no effect of each cucurbit species on the architecture of established strawberry plants, regardless of planting dates.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…2006 and 2007, steadily increasing over time and reaching maximum temperatures above 90°F after Apr. 2006 and2007. Cucurbit planting dates did not affect strawberry aboveground biomass volume as revealed by canopy diameters, which did not change significantly across planting dates, with average diameters of 15.2 and 15.3 inches during 2006 and 2007, respectively (Table 2). This finding indicated that there was no effect of each cucurbit species on the architecture of established strawberry plants, regardless of planting dates.…”
Section: Resultsmentioning
confidence: 95%
“…With regard to intercropping, a previous study found a synergistic yield effect of strawberry intercropped with broad bean (Vicia faba) when fertilized with 80 kgÁha -1 nitrogen (Karlidag and Yildirim, 2007 This is probably due to the effective combination of a nonleguminous crop with a legume. This is a popular intercropping combination in organic and sustainable agriculture.…”
mentioning
confidence: 97%
“…This was probably because faba bean tried to capture more light and thus overcome the strong competition of cereals (indeed, at that stage faba bean plants were high and thin) (data not shown). Karlidag and Yildirim (2007) also reported that intercropping increased plant height of broad bean (Vicia faba L. cv. However, no signifi cant diff erences in plant height were found for any cereal between monocropping and intercropping.…”
Section: Chlorophyll Content and Plant Heightmentioning
confidence: 93%
“…On the other hand, Agegnehu et al (2006) reported that plant height of faba bean in monocropping was similar to that of faba bean in mixtures with barley with 37.5 to 62.6 proportion of faba bean. Karlidag and Yildirim (2007) also reported that intercropping increased plant height of broad bean (Vicia faba L. cv. Lara) compared with broad bean sole cropping.…”
Section: Chlorophyll Content and Plant Heightmentioning
confidence: 93%
“…It has been demonstrated that when maize was intercropped with fava bean, the total yield of both crops was markedly higher than those made of maize or fava bean (Li and others ). Intercropping of wheat or barley with fava bean at a density not lower than 37.5% of fava bean increases total yield and reduces weeds (Agegnehu and others ; ), while intercropping of strawberry with fava bean gave a higher yield (25% to 35%) of marketable strawberries and increased the height of fava bean plants (Karlidag and Yildirim ).…”
Section: General Botanical Featuresmentioning
confidence: 99%